Hepatitis A and Other Associated Hepatobiliary Diseases - Teodor Streba, Costin; Constantin Vere, Cristin; Rogoveanu, Ion; Tripodi, Valeria; Lucangioli, Silvia (IntechOpen, 2020)
Hepatitis A is a major health concern throughout the world. Its impact has largely been limited in recent times by the large-scale use of vaccines. It is, however, still rampant in various parts of the world, partly due to lack of medication, poor water access, and contaminated food products. This book provides comprehensive information on various aspects of hepatitis A with a focus on three of the most important biliary diseases: cholestasis, primary sclerosing cholangitis, and hemophagocytic lymphohistiocytosis. Chapters cover such topics as pathology, epidemiology, at-risk populations, animal research models, and future trends.